Overseas GPs and Prescription Behaviour in England - Catia Nicodemo; Cristina E. Orso; Cristina Tealdi (Institute of Labor Economics (IZA), 2023)
The UK imports many doctors from abroad, where medical training and experience might be different. This study attempts to understand how drug prescription behaviour differs in English GP practices which have larger or smaller numbers of foreign-trained GPs. Results show that in general practices with a high share of GPs trained outside the UK, prescriptions for antibiotics, mental health medication, analgesics and antacids are higher, controlling for the characteristics of the patients and the practices. However, we find no evidence of any significant impact of such different prescribing behaviour neither on patients' satisfaction nor on unplanned hospitalisations, pointing to this behaviour being due to over-prescribing. Identifying differences in prescribing habits among GPs is paramount to identifying the policies best able to guarantee consistent services across GP practices and the consequent reduction of health inequalities.
Keywords: I1; C01; C55; C8; 330; GPs; immigration; prescriptions; NHS England